North Sea Progressive Myoclonus Epilepsy is Exacerbated by Heat, A Phenotype Primarily Associated with Affected Glia. (15th December 2019) - Lambrechts, Roald A.; Polet, Sjoukje S.; Hernandez-Pichardo, Alejandra; van Ninhuys, Lisa; Gorter, Jenke A.; Grzeschik, Nicola A.; de Koning-Tijssen, Marina A.J.; de Koning, Tom J.; Sibon, Ody C.M.
Highlights: North Sea progressive myoclonus epilepsy (NS-PME), a disease caused by mutations in the GOSR2 gene, is exacerbated by heat. Consistently, a Drosophila fruitfly model for NS-PME shows heat-induced seizure-like behavior. Membrin, the Drosophila orthologue of GOSR2, is required in glia, but not in neurons to prevent heat-induced seizures. Sodium barbital treatment to NS-PME flies decreased heat-induced seizures. The fly model can be used to understand the pathophysiology of NS-PME and to identify treatment strategies. Abstract: Progressive myoclonic epilepsies (PMEs) comprise a group of rare disorders of different genetic aetiologies, leading to childhood-onset myoclonus, myoclonic seizures and subsequent neurological decline. One of the genetic causes for PME, a mutation in the gene coding for Golgi SNAP receptor 2 ( GOSR2 ), gives rise to a PME-subtype prevalent in Northern Europe and hence referred to as North Sea Progressive Myoclonic Epilepsy (NS-PME). Treatment for NS-PME, as for all PME subtypes, is symptomatic; the pathophysiology of NS-PME is currently unknown, precluding targeted therapy. Here, we investigated the pathophysiology of NS-PME. By means of chart review in combination with interviews with patients ( n  = 14), we found heat to be an exacerbating factor for a majority of NS-PME patients (86%). To substantiate these findings, we designed a NS-PME Drosophila melanogaster model. Downregulation of the Drosophila GOSR2-orthologue Membrin leads to heat-induced seizure-like behaviour. Specific downregulation of GOSR2/Membrin in glia but not in neuronal cells resulted in a similar phenotype, which was progressive as the flies aged and was partially responsive to treatment with sodium barbital. Our data suggest a role for GOSR2 in glia in the pathophysiology of NS-PME.